2017
DOI: 10.1177/8755122517750398
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Alpha-Blockers for Kidney Stones in Adults

Abstract: Kidney stones are a common and growing problem in the United States. A recent survey found that 11% of men and 7% of women will experience at least one kidney stone in their lifetime. Recurrence is estimated to be ≤50% at 5 years. Risk factors include male gender, obesity, diabetes, gout, and income less than $75 000. Noncontrast computed tomography imaging is typically used to confirm diagnosis and estimate stone size. Pain is the most common symptom and occurs when the stone attempts to pass through the uret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Although the inclusion criterion for the present study was not limited to the presence of distal ureter stones on computed tomography scans as in human studies [ 24 , 25 ], the findings of this study suggest that medical treatment with tamsulosin may be a safe option for feline patients with small distal ureter stones. If the cases included are only with stones in the distal ureter, a higher treatment success rate is expected.…”
Section: Discussionmentioning
confidence: 99%
“…Although the inclusion criterion for the present study was not limited to the presence of distal ureter stones on computed tomography scans as in human studies [ 24 , 25 ], the findings of this study suggest that medical treatment with tamsulosin may be a safe option for feline patients with small distal ureter stones. If the cases included are only with stones in the distal ureter, a higher treatment success rate is expected.…”
Section: Discussionmentioning
confidence: 99%
“…The use of alpha-1 blockers may also be a good option in these cases. However, there is evidence that this class of drugs promotes various adverse effects, including renal adverse ones 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Alpha receptor blockage inhibits basal smooth muscle cell tonus and hyperperistaltic wave frequency (6). Various studies have shown that alpha-blockers accelerate stone excretion and facilitate stone passage by causing relaxation of the smooth muscles of the ureteral wall (7,8).…”
Section: Introductionmentioning
confidence: 99%